2005
DOI: 10.1037/0882-7974.20.4.579
|View full text |Cite
|
Sign up to set email alerts
|

No aging bias favoring memory for positive material: Evidence from a heterogeneity-homogeneity list paradigm using emotionally toned words.

Abstract: Some authors argue for a memory advantage of older adults for positively toned material. To investigate the contribution of selective processing to a positivity effect, the authors investigated young (n = 72, aged 18 to 31) and older (n = 72, aged 64 to 75) adults' memory for emotionally toned words using a multitrial paradigm that compares performance for heterogeneous (mixed valence) and homogeneous (single valence) lists. Regarding the age comparison, there was no evidence for an aging bias favoring positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
141
6
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 46 publications
18
141
6
4
Order By: Relevance
“…While the results of this and many other studies (Knight et al, 2007;Kwon et al, 2009;Mather and Carstensen, 2005) indicate a positivity bias in older adults, this effect is not always seen (e.g., Grühn et al, 2005;Isaacowitz et al, 2006). The emergence of the positivity effect can be reversed when attentional resources become limited for example (Knight et al, 2007), perhaps indicating that emotional goals are prioritized only when there are enough attentional resources available.…”
Section: Discussionmentioning
confidence: 72%
“…While the results of this and many other studies (Knight et al, 2007;Kwon et al, 2009;Mather and Carstensen, 2005) indicate a positivity bias in older adults, this effect is not always seen (e.g., Grühn et al, 2005;Isaacowitz et al, 2006). The emergence of the positivity effect can be reversed when attentional resources become limited for example (Knight et al, 2007), perhaps indicating that emotional goals are prioritized only when there are enough attentional resources available.…”
Section: Discussionmentioning
confidence: 72%
“…However, some studies suggest that there is a "positivity effect," where older adults may be more likely to attend to and remember positive information (Mather and Carstensen 2005;Wong et al 2012). On the other hand, some studies have suggested that older adults are biased toward remembering negative details (Kensinger et al 2007) or show no evidence of such an age-related positivity bias (Grühn et al 2005;Fernandes et al 2008). One potential source of conflict is that aging is not a uniform phenomenon and individual differences are frequently observed in older adults.…”
mentioning
confidence: 84%
“…finding of a greater bias or positivity eVect for mixed lists relative to lists that contain only positive or negative information (e.g., Grü hn, Smith, & Baltes, 2005). However, although emotional materials lend themselves well to the model in terms of evaluative processing and priority, in the following section other domains of impaired memory performance will be covered, in order to illustrate how the evaluative processing (as described in the model) can account for some important findings in the literature, especially in terms of the strategic control that is used by older adults.…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 99%